Late Presentation of Cauda Equina Syndrome with Isolated Bladder Bowel Incontinence in Massive Lower Lumbar Disc Herniation: A Series of Three Cases - Kiran Dhole; Kuber Sakhare; Nilesh Sakharkar; Pravin Agrawal; Sumedh Chaudhary; Vishal Giri (Journal of Orthopaedic Case Reports)
Introduction: Cauda equina syndrome (CES) is a constellation of symptoms that include lower limb paralysis, saddle anesthesia, bowel bladder incontinence, and sexual dysfunction. However, atypical cases of CES may present with isolated bladder-bowel involvement without motor weakness. This often leads to late patient presentation to an orthopedic surgeon and late surgical intervention. Surgical outcomes in such cases are unpredictable owing to chronic bladder incontinence. The purpose of this case series is to evaluate the effect of surgical decompression in delayed presentation of CES with isolated bladder bowel involvement. Case Report: We attended three such patients at our institute with massive lumbar disc herniation. All of them had bladder and bowel dysfunction with the absence of lower limb weakness. Patients were operated with conventional laminectomy and discectomy. Bladder ultrasonography was done preoperatively and postoperatively. Bladder and bowel function improved in all three patients, but recovery duration was different in all three cases. Conclusion: Atypical presentation of CES presenting to other broad specialties, especially urology, may not detect massive lumbar disc herniation in the absence of lower limb deficit. Clinicians should be highly suspicious about the isolated presentation of CES and refer to spine surgeons. Thus, surgical decompression of massive lumbar disc prolapse can be done in the initial stages of bladder-bowel dysfunction. Surgical decompression is effective in delayed presentation of CES with good long-term prognosis.